ANALISIS PENERAPAN STRATEGI PEMBELAJARAN KONTEKSTUAL DI KELAS IV SD NEGERI 46 CAKRANEGARA - Ilmi, Nurul; Kusumasari, Ni Made; Salsabila, Naola; Islamiyati, Nafiysah; Deviawati, Putri; Latief, Nabila; Istiningsih, Siti; Putri, Hikmah Ramdhani (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
Education plays an important role in shaping the character and competence of students so that they are able to face real life challenges. In the context of basic education, the learning strategy used by teachers greatly determines the success of the teaching and learning process. One approach that is considered effective in increasing student engagement and understanding is the contextual learning strategy or Contextual Teaching and Learning (CTL). Therefore, this study aims to analyze the application of contextual learning strategies in Class IV of SDN 46 Cakranegara. The method used in this study is descriptive qualitative which aims to describe the application of contextual learning strategies in class IV of SDN 46 Cakranegara. The subjects of the study were homeroom teachers and class IV students of SDN 46 Cakranegara. In this study, data collection was carried out by means of observation, interviews and documentation of learning activities in class IV of SDN 46 Cakranegara. The results of the study showed that class IV teachers of SDN 46 Cakranegara had a good understanding of contextual learning strategies (CTL). This understanding is not only limited to theoretical aspects, but also to the practical implementation of CTL as an approach that emphasizes the relationship between subject matter and students' real experiences. Teachers realize the importance of their role as facilitators in creating an active, meaningful, and contextual learning process, in line with the principles of constructivism. This understanding is reflected in the teacher's awareness in designing learning activities that involve students emotionally and cognitively through linking materials to local culture and the use of relevant media.